Intravesical injections of autologous platelet‐rich plasma for the treatment of refractory interstitial cystitis - Kuo, Hann‐Chorng (Lower urinary tract symptoms, 2023)
The urothelium acts as a barrier for the urinary bladder that prevents the influx of urinary toxic substances, electrolytes, urea nitrogen, and pathogens into the circulation. Acute or chronic inflammation of the urinary bladder may impair the regenerative function of urothelial cells and thus urothelial cell differentiation. In an inflamed bladder wall, mature apical cells are defective, resulting in impaired barrier function and thus increased urothelial permeability. This is considered to be the potential mechanism of the symptom trigger in patients with interstitial cystitis/bladder pain syndrome (IC/BPS). Previous studies have revealed that increased bladder inflammation, impaired urothelial cell maturation, a defective umbrella cell barrier, and defective junction proteins are prominent in IC/BPS bladders. Platelet‐rich plasma (PRP) contains many growth factors and cytokines that are essential proteins for modulating inflammation and promoting tissue regeneration and thus wound healing. As such, PRP has been used as a regenerative therapy in many medical fields. Our preliminary studies have demonstrated that multiple intravesical PRP injections could improve symptoms in 70% of IC/BPS patients. Repeated PRP treatments also improve junctional protein, increase cytoskeleton protein expression, and decrease urinary inflammatory proteins. These preliminary results suggest that PRP injections might reduce bladder inflammation and improve urothelial cell regeneration in IC/BPS patients. This article reviews recently published clinical and basic research on the treatment potential of PRP for IC/BPS patients.